2012
DOI: 10.1007/s11357-011-9373-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from case–control and longitudinal studies supports associations of genetic variation in APOE, CETP, and IL6 with human longevity

Abstract: In this study, we investigated 102 singlenucleotide polymorphisms (SNPs) covering the common genetic variation in 16 genes recurrently regarded as candidates for human longevity: APOE; ACE; CETP; HFE; IL6; IL6R; MTHFR; TGFB1; APOA4; APOC3; SIRTs 1, 3, 6; and HSPAs 1A, 1L, 14. In a case-control study of 1,089 oldest-old (ages 92-93) and 736 middle-aged Danes, the minor allele AGE (2013) 35:487-500

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 77 publications
(78 reference statements)
5
50
1
1
Order By: Relevance
“…A post hoc analysis of the APOE epsilon variants and the remaining phenotypes of the present study did not show significance when considering the number of variants tested (data not shown). Moreover, APOE -rs769449, which was associated with longevity in the discovery cohort in our previous study (Soerensen et al, 2013), and was found to be in modest LD (R 2 =0.55) with the APOE ε4 defining variant rs429358 (Soerensen et al, 2013), displayed no significant associations in the present study when considering correction for multiple testing (see Supplementary Table 2). Hence, the lack of association to the aging phenotypes of the present study could imply that rs769449 and the APOE epsilon variants mediate their effects on longevity via other aging related phenotypes than those investigated in the present study, or it could indicate that the effect sizes are too modest to display significance.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…A post hoc analysis of the APOE epsilon variants and the remaining phenotypes of the present study did not show significance when considering the number of variants tested (data not shown). Moreover, APOE -rs769449, which was associated with longevity in the discovery cohort in our previous study (Soerensen et al, 2013), and was found to be in modest LD (R 2 =0.55) with the APOE ε4 defining variant rs429358 (Soerensen et al, 2013), displayed no significant associations in the present study when considering correction for multiple testing (see Supplementary Table 2). Hence, the lack of association to the aging phenotypes of the present study could imply that rs769449 and the APOE epsilon variants mediate their effects on longevity via other aging related phenotypes than those investigated in the present study, or it could indicate that the effect sizes are too modest to display significance.…”
Section: Discussioncontrasting
confidence: 55%
“…The selection of genes and gene variants, and the generation of genotype data in the discovery sample are described in detail in (Soerensen et al, 2012, Soerensen et al, 2013 and Supplementary Information). The SNPs were primarily chosen to be tagging SNPs with an R 2 >0.8.…”
Section: Methodsmentioning
confidence: 99%
“…Investigations of both monogenic CETP deficiency and polymorphisms in the CETP gene provided controversial evidence. Some studies reported reduced cardiovascular disease risk and prolonged life expectancy in individuals with CETP mutants, [193][194][195][196] others did not find any impact or even increased cardiovascular risk. 197,198 Previous meta-analyses of genetic studies, provided compelling evidence that polymorphisms that are associated with reduced CETP activity and increased HDL-cholesterol levels are also associated with reduced cardiovascular risk.…”
Section: Fibratesmentioning
confidence: 98%
“…Interestingly, Poolseq with target region including regulatory region such as proximal upstream and intronic region identified longevity-associated common variants, rs405509 and rs769449 that were previously associated with longevity and other aging-related disease phenotypes (Lu et al, 2014; Soerensen et al, 2013). They are also predicted (Supplementary Figure 2) and experimentally proved (Supplementary Table 3) to be functional, implicating the potential role of regulatory variants in a longevity-association.…”
Section: Descriptionmentioning
confidence: 99%